2011
DOI: 10.1021/om100891m
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Molybdenum-Mediated Acrylate Formation from Carbon Dioxide and Ethylene

Abstract: A zerovalent molybdenum complex, [(Ph 2 PCH 2 CH 2 ) 2 PPh]Mo(C 2 H 4 )(N 2 ) 2 , was found to promote coupling of CO 2 and ethylene to afford a molybdenum(II) acrylate hydride complex. The identity of the molybdenum(II) acrylate hydride complex was established by spectroscopy and reactivity studies. The mechanism of carbon dioxide functionalization with ethylene has been investigated by a series of kinetic and isotopic labeling studies, in addition to the observation of a formally molybdenum(0) carbon dioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 53 publications
2
29
0
2
Order By: Relevance
“…Theoretical studies on the absorption, catalysis, and activation of the CO 2 molecule have been reported [9][10][11][12][13][14][15][16][17][18]. In the present paper, I provide a systematic theoretical study of the bonding features, hyperconjugation, and electronic structures of a series of transition metal CO 2 complexes with various coordination models.…”
Section: Introductionmentioning
confidence: 93%
“…Theoretical studies on the absorption, catalysis, and activation of the CO 2 molecule have been reported [9][10][11][12][13][14][15][16][17][18]. In the present paper, I provide a systematic theoretical study of the bonding features, hyperconjugation, and electronic structures of a series of transition metal CO 2 complexes with various coordination models.…”
Section: Introductionmentioning
confidence: 93%
“…For the more oxophilic molybdenum, lactone formation occurs via prior formation of a stable CO 2 -ethylene complex by ligand exchange and by subsequent coupling of CO 2 and ethylene. 37,38 Lactones of other metals than nickel resulting from the direct coupling of CO 2 , and alkenes, alkynes, alkadienes, or allenes have only been described for an allene (a single palladalactone), 39 nevertheless, as a substance class they are known. 12,14 We have focused our experimental activities on bidentate ligands, such as bisphosphines.…”
Section: Shedding Light Into the Dark: Lactone Formation 21 Lactone mentioning
confidence: 99%
“…Bernskoetter et al zeigten jedoch kürzlich anhand von NMR-spektroskopischen Experimenten, dass bei der Reaktion von Molybdän(0)-Ethylen-Komplexen mit CO 2 sowohl Ethylen als auch CO 2 p-gebunden am Molybdänatom koordinieren, bevor sie zum Molybdalacton kuppeln und sich schließlich zu einem Acrylatliganden umlagern (siehe Abschnitt 3.1.2). [19] Die saure Hydrolyse von Nickelalactonen führt zur Protonierung des Liganden, d. h. zur Zersetzung des Nickelkomplexes und zu freier Carbonsäure. Seitdem wurden nur die Produkte der Umwandlung von CO 2 und Olefinen nach Hydrolyse oder Methanolyse unter Bildung von Carbonsäuren bzw.…”
Section: Koordination Von Co 2 An üBergangsmetallkomplexeunclassified
“…[30] Die komplexvermittelte oxidative Kupplung von CO 2 [36,37] Erst kürzlich wurde von Bernskoetter und Tyler gezeigt, dass [{(Ph 2 PCH 2 CH 2 )PPh}Mo(N 2 ) 2 (C 2 H 4 )] mit CO 2 analog reagiert. [19] [41] oder Pyridin [42] synthetisiert, jedoch mit unbefriedigenden Ergebnissen. [43] 2007 präsentierten Buntine und Mitarbeiter DFT-Rechnungen, denen zufolge die Bildung von Nickelhydriden aus der b-H-Eliminierung von Nickelalactonen wegen der Ringspannung und des weiten Abstandes von b-H-Atomen zum Nickelzentrum energetisch ungünstig ist.…”
Section: Koordination Von Co 2 An üBergangsmetallkomplexeunclassified